Lymphocytes Apoptosis in Patients with Acute Exacerbation of Asthma - Agnès Hamzaoui; Kamel Hamzaoui; Habib Salah; Abdellatif Chabbou (Hindawi Limited, 1999)
Asthma is characterized by airway inflammation, which can be now assessed by the analysis of induced sputum . Ten patients with asthma were investigated during acute exacerbation for the quantification of apoptosis, for Bcl-2 and Fas expression, in induced sputum lymphocytes. They were compared to 12 patients with chronic obstructive pulmonary disease (COPD), and 10 healthy controls. Spontaneous apoptosis was determined by staining nuclei with propidium iodide, and analyzed with a FACScan. Bcl-2 was measured by Western blotting, and results were obtained by densitometric scanning, done by the gel proanalyser. The investigation of Fas was performed using the streptavidin-biotin preroxidase-complex method. Patients with asthma and patients with COPD exhibited a significant increase of cellularity, percentage of neutrophils, eosinophils and lymphocytes when compared to healthy controls. Apoptosis in induced sputum mononuclear cells was found decreased in patients with asthma compared to COPD patients and healthy controls. The quantification of apoptosis was measured after exposure to anticytokine antibodies. Anti-TNF-α antibody blocked the apoptosis in both patients groups and healthy controls, suggesting that TNF-α acted as an inducer of apoptosis. Anti-IL-10 blocked apoptosis completely exclusively in patients with asthma. Bcl-2 expression was found to be increased in induced sputum mononuclear cells from patients with asthma, compared to healthy controls and patients with COPD. Expression of Fas could be detected in patients with asthma, at a lower level than COPD patients and healthy controls. Distinct mechanisms of apoptosis were found in patients with asthma and patients with COPD, characterized by different levels of Bcl-2 and Fas expression. Induction of apoptosis should be a beneficial process in allergic inflammation traduced in induced sputum mononuclear cells. The apoptosis process is assumed by two different mechanisms in asthma and COPD. Our findings indicated that in asthmatic patients, activated lymphocytes accumulate in the bronchi; because of their prolonged survival that maintains inflammation.